Let f(x) = 2x + 2. Solve f−1(x) when x = 4.
Let f(x) = x + 8 and g(x) = x2 − 6x − 7. Find f(g(2)).
Let f(x) = x2 − 8x + 5. Find f(−1).
Answer:
Part 1) and
Find f(g(x)).
Substitute value of g(x) in place of x
So,
Part 2)
Replace y with x and x with y
Find y
So,
Substitute x = 4
Part 3) and
Substitute value of g(x) in place of x
Substitute x = 2
Part 4)
Substitute x = -1
Answer:
27
Step-by-step explanation:
Hello,
do you agree that
?
Then,
we can simplify as below and multiply by 9 both sides and divide by 2
Thanks
sin x = sqrt(3)/2
Answer:
Step-by-step explanation:
We are given that
We have to find all solutions of the given equation
We know that
sin x is positive then the value of sin x will lie in I quadrant and II quadrant.The value of sin x is negative in III and IV quadrant .
We are given that sin x is positive then the solution will lie in I and II quadrant only.Therefore, the solution of sin x will not lie in III and IV quadrant .
...(I equation )and ...(II equation)
In II quadrant change into
Cancel sin on both side of equation I
Then, we get
...(II equation )
Cancel sin on both side of equation II
Then we get
Hence, the solutions of equation are
The solutions of the equation are:
x = 60 degrees
x = 120 degrees
x = 420 degrees
x = 480 degrees, and so on.
We have,
The solutions to the equation sin(x) = √3/2 are any angles where the sine of the angle is equal to √3/2.
So,
sin 60 = √3/2
sin 120 = sin (π - 60) = sin 60 = √3/2
In trigonometry 180 is written as π.
Since (π - 60) is in the secondquadrant sin 60 is positive.
sin 420 = sin (360 + 60) = sin 60 = √3/2
In trigonometry 360 is written as 2π.
Since (2π + 60) is in the Firstquadrant sin 60 is positive.
Similarly,
sin 480 = sin (2π + 120) = sin 120 = sin (π - 60) = sin 60 = √3/2
Thus,
The solutions of the equation are:
x = 60 degrees
x = 120 degrees
x = 420 degrees
x = 480 degrees, and so on.
Learn more about solutionsofequations here:
#SPJ6
What is the additive inverse function of f(x)?
A. g(x) = –3x^2 – 4
B. g(x) = –4x^2 – 3
C. g(x) = 3x^2 – 4
D. g(x) = 4x^2 + 3
Answer:C
Step-by-step explanation:
Answer:c:g(x)=3x^2-4
Step-by-step explanation:
b. 3 must be a factor of a or of b
c. 3 must be a factor of a and of b
please help and show work